Retinal Vessel Diameter Changes in COVID-19 Infected Patients - Aşıkgarip, Nazife; Temel, Emine; Hızmalı, Lokman; Örnek, Kemal; Sezgin, Fikriye Milletli (Ocular immunology and inflammation, 2021)
Purpose: To evaluate the longitudinal changes in retinal vessel diameters in patients with coronavirus disease 2019 (COVID-19). Methods: This study included 25 patients with COVID-19 (Group 1) and 25 healthy subjects (Group 2). The diameters of peripapillary temporal and nasal retinal arteries and veins were measured at baseline and at 4 months after remission. Results: The baseline diameters of the inferior temporal vein and the artery were increased in group 1 compared to controls (p = .007 and p = .041, respectively). There was also an increase in the diameters of the inferior and superior nasal veins and arteries in group 1 at baseline (p = .001, p = .019, p = .037, and p = .008, respectively). Retinal vessel diameters decreased after remission in all quadrants in comparison to baseline measurements (all p < .05). Conclusion: Increased retinal vessel diameters were measured in COVID-19 patients during the disease. Measurement of retinal vessel diameters may be a noninvasive method of estimating the vascular risk.